Hepatic Encephalopathy and Liver Transplantation: The Past, Present, and Future Toward Equitable Access. Issue 12 (24th September 2021) - Acharya, Chathur; Bajaj, Jasmohan S.
Abstract : Cirrhosis is a debilitating chronic disease with high morbidity and mortality, with the only real cure being liver transplantation (LT). Currently, we allocate organs for transplantation based on the Model for End‐Stage Liver Disease–Sodium (MELD‐Na) score that does not account for hepatic encephalopathy (HE). HE affects patients, families, and the health care system because of high rates of recurrence and major readmission burden. Moreover, HE casts a long shadow even after LT. Accounting for HE and incorporating it into the current allocation system has many proponents, but the framework to do this is currently lacking because of differences in consensus or in operationalization parameters. We review the latest evidence of the burden of HE, management of HE before and after LT, and evaluate pros and cons of several methods of diagnosing HE objectively to ensure early and equitable access to LT in this underserved population. Abstract : https://www.wileyhealthlearning.com/#/online-courses/e62e415a-f0d3-4f68-8d16-14e1f69380af